Rancangan Paket Wisata Tailor Made untuk Accessible Tourism di Bali: Inovasi Biro Perjalanan Wisata - Jesy Valenia Panggabean; Made Budiarsa; Denok Lestari (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
Accessible tourism has become an increasingly urgent need as awareness of the rights of persons with disabilities, the elderly, and other travelers with special needs grows. Although Indonesia, particularly Bali, has enormous potential as a tourism destination, implementing inclusive principles in travel services still faces numerous challenges. This study aims to design a tailor-made travel package based on accessible tourism as a destination management company innovation to address accessibility issues and realize inclusive tourism in Bali. This research applied a qualitative descriptive method using a case study approach. Data were collected through observation, in-depth interviews with tourism stakeholders, including destination management companies, travelers with special needs, and local partners, as well as field documentation. The research was conducted in Bali as the tourist destination region and the Netherlands as the traveler-generating region, with a focus on the destination company management, Jewel Indonesia Tour and Travel. Findings show that destination management companies still face challenges such as inaccessible infrastructure, limited staff knowledge, and a lack of understanding of universal design concepts. However, there are significant opportunities through niche market demands, national regulatory support, and collaboration with disability communities and international partners. The developed travel package includes inclusive accommodations, disability-friendly activities, accessible transportation, and digital information adapted to user needs. This research significantly contributes to the existing literature gap regarding the role of destination management companies in accessible tourism. Furthermore, the designed model is expected to serve as a best practice framework for developing inclusive tourism products in other destinations across Indonesia. The study concludes that a customer-centered approach, cross-sector collaboration, and sustainable innovation are crucial in building an equitable tourism ecosystem. It is recommended that tourism stakeholders enhance accessibility education and integrate universal design principles into all tourism services.